Vitamin D-Mediated Anti-cancer Activity Involves Iron Homeostatic Balance Disruption and Oxidative Stress Induction in Breast Cancer - Bajbouj, Khuloud; Sahnoon, Lina; Shafarin, Jasmin; Al-Ali, Abeer; Muhammad, Jibran Sualeh; Karim, Asima; Guraya, Salman Y.; Hamad, Mawieh (Frontiers in Cell and Developmental Biology, 2021)
Background: Vitamin D deficiency associates with high risk of breast cancer (BRCA) and increased cellular iron. Vitamin D exerts some of its anti-cancer effects by regulating the expression of key iron regulatory genes (IRGs). The association between vitamin D and cellular iron content in BRCA remains ambiguous. Herein, we addressed whether vitamin D signaling exerts a role in cellular iron homeostasis thereby affecting survival of breast cancer cells. Methods: Expression profile of IRGs in vitamin D-treated breast cancer cells was analyzed using publicly available transcriptomic datasets. After treatment of BRCA cell lines MCF-7 and MDA-MB-231 with the active form of vitamin D, Labile iron content, IRGs protein levels, oxidative stress, and cell survival was evaluated. Results: Bioinformatics analysis revealed several IRGs as well as cellular stress relates genes were differentially expressed in BRCA cells. Vitamin D treatment resulted in cellular iron depletion and differentially affected the expression of key IRGs protein levels. Vitamin D treatment exerted oxidative stress induction and alteration in the cellular redox balance by increasing the synthesis of key stress-related markers. Collectively, these effects resulted in a significant decrease in BRCA cell survival. Conclusion: These findings suggest that vitamin D disrupts cellular iron homeostasis leading to oxidative stress induction and cell death.